Surfactant-assisted alkaline pretreatment and enzymatic hydrolysis of Miscanthus sinensis for enhancing sugar recovery with a reduced enzyme loading - Cheng, Xiyu; Luo, Ying; Gao, Yifan; Li, Shen; Xu, Chunming; Tang, Shangyuan; Yang, Yongkun; Zhang, Zehua; Jiang, He; Xu, Hanli; Shi, Shuobo; Yan, Qiong (Frontiers in Bioengineering and Biotechnology, 2022)
Surfactants play a vital role in the delignification and saccharification of lignocellulosic biomass. A strategy for coupling surfactant-assisted alkaline pretreatment (SAP) with surfactant-assisted enzymatic hydrolysis (SEH) has been proposed for improving sugar recovery from a potential energy crop, Miscanthus sinensis. Poly (ethylene glycol) 2000 (PEG 2000) was found to be more efficient in SAP than in other tested surfactants. Compositional and structural analysis revealed that the SAP process with 1% of PEG 2000 produced more efficient lignin removal and microstructure disruption of the pretreated sample, thus indicating much higher reducing sugar yields of 544.4-601.2 mg/g compared to the samples that were untreated or pretreated by alkali alone. Moreover, SEH with 1% Tween 80, which could block the lignin-enzyme interactions, produced a substantial reduction of 33.3% in the enzyme loading to achieve a higher sugar recovery from the SAP sample.